Patients' sense of medical gain on family doctor contracting services in China: scale development and preliminary validation - Jiaqi Zhang; Cuihong Ou; Yuxi Liu; Yufeng Chen; Tufen He; Ruiming Liu (BMC Health Services Research)
Abstract Background and aim The system of family doctor contract services is a crucial component of China's primary healthcare system. Patients enrolled in family doctor contract services typically receive more comprehensive health services. However, it remains uncertain whether the family doctor contract services can fully meet the healthcare needs of patients. Despite extensive research on family doctor contract services, there has been relatively little investigation from the perspective of patients' sense of gain, and there are no specific tools available to measure patients' sense of gain in healthcare. Therefore, this study aims to develop a scale to measure patients' sense of gain in family doctor contract services. Methods This study enrolled 600 patients under family doctor contracts. It utilized a review of literature and Delphi expert consultation to form the concept of patients' sense of medical gain in the context of family doctor services, establish an item pool, screen items, and evaluate the scale's reliability and validity. Factor analysis assessed the scale's structural validity, while Cronbach's alpha coefficient evaluated its internal consistency. Test–retest reliability and split-half reliability were used to assess the scale's reliability. Results The Patients' Sense of Medical Gain in the context of Family Doctor services(PSMG-FD) scale for assessing sense of medical gain among family doctor contract patients comprises 19 items, categorized into five factors: Medical convenience, continuity, reliability, humanistic care, and experience. Confirmatory factor analysis results indicated satisfactory fit indices: χ2/df = 2.781, RMSEA = 0.077, RMR = 0.031, GFI = 0.875, NFI = 0.918, IFI = 0.946, TLI = 0.934, CFI = 0.945, and RFI = 0.901. The AVE values for different dimensions were 0.544, 0.739, 0.741, 0.755, and 0.654, all surpassing the threshold of 0.5. The CR values for each dimension were 0.820, 0.919, 0.919, 0.925, and 0.850, all exceeding 0.7, indicating satisfactory convergent validity. The interdimensional correlation coefficients were lower than the square roots of the corresponding AVEs, suggesting correlation among latent variables while maintaining sufficient discriminant validity. The PSMG-FD scale demonstrated good reliability and validity, with a Cronbach’s α coefficient of 0.947, test–retest reliability of 0.955, and split-half reliability of 0.895. Conclusion The scale exhibits good reliability and validity, making it a suitable instrument for evaluating sense of medical gain among family doctor contract patients in China.